Students` Vocabulary Mastery After Applying Quantum Teaching Model In Module - Ardiansya, Ardiansya (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
This research based on the problem regard English especially vocabulary mastery of the students. Students are most likely could not say something because they are lack of vocabulary and then students put in their mindset if English is one of the most difficult subject in this case. Applying quantum teaching model in module to improve the vocabulary mastery is suggested to solve the problem. The objectives of the research is to find out and analyze whether or not the Applying of quantum teaching model in module improve or not the students vocabulary mastery of the tenth grade students of SMK Negeri 3 SIDRAP. The researcher applied quasi-experimental design. The sample of the research was 38 students from two classes which taken from the population of the tenth grade students of SMK Negeri 3 SIDRAP. The researcher gave treatment based on the material that already formulated into some module and the test of the research was vocabulary test. The resulting of the data analysis shows that t-test value in post-test was 2.081 and the t-table value 2.028. Therefore, the students who taught trough Quantum Teaching Model in Module were better than the students who taught Contextual Learning Model.